Nanoparticles—Emerging Potential for Managing Leukemia and Lymphoma - Vinhas, Raquel; Mendes, Rita; Fernandes, Alexandra R.; Baptista, Pedro V. (Frontiers in Bioengineering and Biotechnology, 2017)
Nanotechnology has become a powerful approach to improve the way we diagnose and treat cancer. In particular, nanoparticles possess unique features for enhanced sensitivity and selectivity for earlier detection of circulating cancer biomarkers. In vivo, nanoparticles enhance the therapeutic efficacy of anticancer agents when compared to conventional chemotherapy, improving vectorization and delivery, and helping to overcome drug resistance. Nanomedicine has been mostly focused on solid cancers due to take advantage from the enhanced permeability and retention (EPR) effect experienced by tissues in the close vicinity of tumors, which enhance nanomedicine’s accumulation and, consequently, improve efficacy. Nanomedicines for leukemia and lymphoma, where EPR effect is not a factor, are addressed differently from solid tumors. Nevertheless, nanoparticles have provided innovative approaches to simple and non-invasive methodologies for diagnosis and treatment in liquid tumors. In this review, we consider the state of the art on different types of nanoconstructs for the management of liquid tumors, from pre-clinical studies to clinical trials. We also discuss the advantages of nanoplatforms for theranostics and the central role played by nanoparticles in this combined strategy.